Risk of Cardiovascular Disease in Women With a History of Hyperemesis Gravidarum, With and Without Preeclampsia - Bianca Cécile; Brian J. Potter; Antoine Lewin; Jessica Healy‐Profitós; Émilie Brousseau; Nathalie Auger (Journal of the American Heart Association: Cardiovascular and Cerebrovascular Disease)
Background Hyperemesis gravidarum is associated with preeclampsia, but it is unclear whether hyperemesis gravidarum is a risk factor for cardiovascular disease. We assessed the long‐term risk of cardiovascular disease in women who experienced hyperemesis gravidarum with or without preeclampsia. Methods and Results We analyzed a longitudinal cohort of 1 413 166 pregnant women in Quebec between 1989 and 2021. Women were followed from their first pregnancy up to 3 decades later. We computed hazard ratios (HRs) and 95% CIs for the association of hyperemesis gravidarum, preeclampsia, or both conditions with subsequent risk of cardiovascular hospitalization using Cox regression models adjusted for baseline characteristics. Among 1 413 166 women, 16 288 (1.2%) had hyperemesis gravidarum only, 69 645 (4.9%) preeclampsia only, and 1103 (0.08%) had both conditions. After 32 years of follow‐up, cardiovascular disease incidence was 17.7 per 100 women with hyperemesis gravidarum only, 28.2 per 100 women with preeclampsia only, 30.9 per 100 women with both exposures, and 14.0 per 100 women with neither exposure. Compared with no exposure, women with both hyperemesis and preeclampsia had the greatest risk of cardiovascular hospitalization (HR, 3.54 [95% CI, 3.03–4.14]), followed by women with preeclampsia only (HR, 2.58 [95% CI, 2.51–2.64]) and hyperemesis only (HR, 1.46 [95% CI, 1.38–1.54]). Having both hyperemesis gravidarum and preeclampsia was strongly associated with valve disease (HR, 3.38 [95% CI, 1.69–6.75]), heart failure (HR, 3.43 [95% CI, 1.79–6.59]), and cardiomyopathy (HR, 4.17 [95% CI, 1.99–8.76]). Conclusions Hyperemesis gravidarum is associated with the development of cardiovascular disease, whether preeclampsia is present or not.